SISTEM INFORMASI PENOMORAN KARTU BON KOPKARBARA PT.BUKIT ASAM (PERSERO) TBK, BANDAR LAMPUNG BERBASIS WEB - Alhibarsyah Alhibarsyah (Industrika : Jurnal Ilmiah Teknik Industri, 2019)
To achieve an objective of this card numbering information system is to be computerized with a system that is capable of producing the right output, and also a quick solution. To support the needs of the workers in PT. Bukit Asam Tbk, a small company was established under the auspices of PT. Bukit Asam Tbk, the Kopkarbara Cooperative Shop, where the store provided good employee needs and outsourcing using the Extreme Programming Method. In carrying out its activities, PT. Bukit Asam's cooperative still uses an ineffective delivery medium so that it cannot regulate the maximum number of employee demand, this can damage the company because it can not control the maximum number of bon at PT. Bukit Asam's cooperative. From the development of the old system to the new system obtained from the application program that can solve all problems on the old system, with the creation of a web-based application program, this program can overcome the difficulties in the numbering information system, Increase the demand for ordering numbers or goods and this application program can help for divisions. to get online. Keywords: System, Information, Website, Extreme, Programming